2012
DOI: 10.6088/ijes.00202030031
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation of heavy metals by Trifolium alexandrinum

Abstract: The release and persistence of toxic heavy metals into the natural environment is a serious concern especially in urban areas. The problem of heavy metal pollution is gaining momentum from year to year as more and more amounts of heavy metals are extracted from their ores and released into the environmental segments (water, air and soil) during processing or afterwards. Heavy metals are essentially nonbiodegradable and therefore accumulate in the environment and subsequently find their way into the food chains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Roots accumulated more metals than leaves and stems, indicating low translocation from the root to the aerial part of the plant (ALI et al, 2012). In addition, the results confirmed that Cu and Zn are deemed to have low mobility in plants (MARSCHNER, 2012).…”
Section: Discussionmentioning
confidence: 68%
“…Roots accumulated more metals than leaves and stems, indicating low translocation from the root to the aerial part of the plant (ALI et al, 2012). In addition, the results confirmed that Cu and Zn are deemed to have low mobility in plants (MARSCHNER, 2012).…”
Section: Discussionmentioning
confidence: 68%
“…The study of Lion et al (2016) observed that from all the plants studied, the concentrations of trace metals in the roots were more than those recorded in the shoot with a significant difference (p<0.05). Hazrat et al (2012) showed that the concentrations of trace metals were greater in roots than in shoots. A similar observation was also made by Peralta et al (2001) where alfalfa plants accumulated more of the trace metals in the roots than any other part.…”
Section: Plant Partsmentioning
confidence: 99%
“…The bioconcentration factor and translocation factors were calculated as per procedure of Hazrat et al (2012). The bioconcentration factor (BCF) and translocation factor (TF) data was then log transformed and then analysed for Pearson correlation coef- …”
Section: Discussionmentioning
confidence: 99%